The analgesic effect of lumbar sympathetic ganglion block in patients with failed back surgery syndrome - Lee, Jin Young; Sim, Woo Seog; Kim, Jiyoung; Yang, Sungwon; Ro, Hojun; Kim, Chang Jae; Kim, Sung Un; Park, Hue Jung (Frontiers in Medicine, 2023)
Background: Persistent or recurrent lumbosacral pain is a common symptom after spinal surgery. Several interventions have been introduced for failed back surgery syndrome; however, their clinical efficacy, safety, and cost-effectiveness are insufficient. Sympathetic ganglion block has been selected for pain associated with sympathetic nervous system. In this study, we compared pain and quality of life in responder and non-responders of lumbar sympathetic ganglion block in failed back surgery syndrome. Methods: We included 84 patients diagnosed with failed back surgery syndrome and had lumbosacral pain who underwent lumbar sympathetic ganglion block between January 2020 and April 2021. The patients’ data were retrospectively analyzed; clinical outcomes were assessed before (T0), 1 week after (T1), and 4 weeks after (T4) lumbar sympathetic ganglion block. Based on the pain difference from T0 to T1, we categorized patients into two groups: patients with ≥50% pain reduction (responder group) and patient with <50% pain reduction (non-responder group). Demographic, clinical, surgical, and fluoroscopic data were evaluated and compared. The primary outcome was pain scores and EuroQol-5D score from T0 to T4. Results: Among the 84 patients analyzed, 41 (48.8%) experienced ≥50% pain reduction. Lumbar sympathetic ganglion block significantly improved pain at T1 and T4 compared to T0 in both groups. Lumbar sympathetic ganglion block improved the EuroQol-5D at T1 compared to T0 in responder group. The responder group had a significant decrease in pain at T1 from T0 and T4 from T0 and a significant decrease in EuroQol-5D at T1 from T0 compared with the non-responder group. Coldness of leg over time did not differ between the group. No serious adverse events occurred in either of the group. Conclusions: Lumbar sympathetic ganglion block may improve pain at 1 and 4 week in patients with failed back surgery syndrome. Patient with ≥50% pain reduction at 1 week showed simultaneous improvement in quality of life and pain reduction at 4 weeks.